Designing and Determining the Psychometric Properties of the Clinical Skills Questionnaire for Operating Room Nursing Students - Reza Mahdavi; Shanaz Pooladi; Masoud Bahreini; Niloufar Motamed; Fatemeh hajinezhad (Kerman University of Medical Sciences, 2017)
Background Clinical education is a major component of nursing programs, and nurses' failure to acquire the necessary clinical skills during their studies compromises the provision of high - quality nursing services in their occupational future. The present study was conducted to design and determine the psychometric properties of the clinical skills questionnaire for operating room nursing students. Methods The present methodological research designed and determined the psychometric properties of the questionnaire in four steps, including defining the concept of clinical skill in nursing students using a book and literature review, designing the questionnaire's items using the available resources in Iran and other countries, assessing face and content validity of the questionnaire by 10 university students and experts, and examining the internal consistency of the questionnaire using Cronbach's alpha. Results The final version of the clinical skills questionnaire, which included 38 items, generated four subscales, including responsibilities of scrub nurse, responsibilities of circulating nurse, recovery room care of patients, and sterilization and infection control. In terms of psychometric properties, we observed a content validity ratio of 0.90, a content validity index of 0.95, and internal consistency showing a Cronbach's alpha of 0.86.The findings confirmed the validity and reliability of the clinical skills questionnaire for operating room nursing students. Conclusions The 38 - item questionnaire has appropriate psychometric properties and can be used in Iran's educational and health systems by educational caregivers. Other validity indices, including construct validity, are recommended to be measured to determine the validity of the questionnaire subscales.